Intravascular ultrasound characteristics in patients with intermediate coronary lesions and borderline fractional flow reserve measurements. Issue 34 (August 2018) - Yang, Hyoung-Mo; Lim, Hong-Seok; Seo, Kyoung-Woo; Choi, Byoung-Joo; Choi, So-Yeon; Yoon, Myeong-Ho; Hwang, Gyo-Seung; Tahk, Seung-Jea
Abstract : Abstract: Revascularization of borderline fractional flow reserve (FFR) is controversial and the morphologic characteristics of borderline FFR lesions are not well known. The objective of this study was to determine the intravascular ultrasound (IVUS) characteristics in intermediate coronary lesions with borderline FFR in patients with intermediate coronary artery stenosis (40%–70% diameter stenosis). Both IVUS and FFR were performed in a total of 228 left anterior descending arteries. We divided them into 3 groups by FFR value: ischemic (n = 46, FFR < 0.75), borderline (n = 71, FFR 0.75 to ⩽0.80), and non-ischemic (n = 111, FFR > 0.80). We compared the IVUS parameters, including minimum lumen area, lesion length, plaque burden, and volumetric analysis among the 3 groups. In the IVUS analysis, the minimum lumen area was smaller (2.5 ± 0.6 vs. 2.7 ± 0.7 vs. 3.4 ± 1.2 mm 2, P < .001); lesion length was longer (23.6 ± 8.4 vs. 23.6 ± 7.4 vs. 17.4 ± 6.8 mm, P < .001); plaque burden was larger (76.1 ± 9.6 vs. 73.9 ± 7.5 vs. 69.8 ± 9.5%, P < .001); plaque volume was larger (173.0 ± 78.3 vs. 167.7 ± 75.0 vs. 129.5 ± 79.1 mm 3, P < .01); and percent atheroma volume was larger (57.9 ± 7.5 vs. 57.6 ± 6.6 vs. 53.9 ± 8.0%, P < .01) in the ischemic and borderline groups compared with the non-ischemic group, respectively. However, post-hoc analyses showed there were no significant differences between the ischemic and borderline group for all IVUS parameters. There were no differences in IVUS characteristics between borderline and functionally significant FFR, but the amount of atheromatous plaque was more severe in these 2 groups than in the non-ischemic group.